HEPATOPROTECTIVE ACTIVITY FROM ETHANOL EXTRACT OF PUGUN TANO'S LEAVE (Curanga fel-terrae (Lour.) Merr.) - Harahap, Urip; Bastian, Marianne; Yuliasmi, Sri; Husori, Dadang Irfan; Patilaya, Popi; Laila, Lia (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study is to observe the activity of ethanol extract of Curanga fel-terrae leave in preventing the damaged of liver which is induced by high dose of paracetamol. Methods: This research was conducted by using Wistar rat divided into 6 groups. Group 1 was the normal group. Group 2, 3, 4, 5 and 6 received CMC-Na 0.5% (negative control), C. fel-terrae ethanolic extract (CFEE) at the doses of 125, 250 and 500 mg/kg, catechin 2 mg/kg (positive control),respectively during 7 days continued and followed by given paracetamol dose of 2.5g/kg 8 hours after that. Hepatoprotective activity was carried out toward parameter of AST, ALT as well as histopathology of the liver. Results: The results showed that high-dose paracetamol dose of 2.5g/kg bw can cause liver damaged which can be seen by the increasing of the level of AST and ALT compared to the normal group (p<0.05). The usage of three doses of CFEEfor 7 days showed the prevention of the increasing of the level of AST and ALT compared to negative control group (p<0.05). Furthermore, the histopathology study revealed that the three doses of extract could protect the liver. Conclusion: The C. fel-terrae ethanolic extract (CFEE) at the doses of 125, 250 and 500 mg/kg bw which was given for 7 days can prevent the liver from the damage caused by high-dose of paracetamol. Keyword: Curanga fel-terrae (Lour.) Merr., paracetamol, liver, hepatoprotective